2018
DOI: 10.1097/md.0000000000012806
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of PCA3 and hK2 in combination with serum PSA for prostate cancer

Abstract: Objectives:The prostate cancer gene 3 (PCA3), human kallikrein 2, and miRNA-141 are promising prostate cancer (Pca) specific biomarkers. Our aim was to evaluate the detection of PCA3, human glandular kallikrein 2 (hk2), and miRNA-141 mRNA in peripheral blood of patients received prostate biopsy. What's more, we want to detect the value of combination of PSA (prostate specific antigen) in the early diagnosis of PCa.Materials and methods:Hundred patients were divided into 2 groups according to the results of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…In an attempt to improve PCa diagnosis, some studies have demonstrated better results of PCA3 in association with PSA [64, 65], in addition to prostate-specific G-protein coupled receptor (PSGR) [66], a biomarker previously described to be overexpressed in PCa tissue [67]. Other authors found that the combination of PCA3 , PSA, and human kallikrein 2 (hK2) largely improved area under the curve (AUC)-receiver operating characteristic (ROC), especially those patients presenting PSA 4-10 ng/mL [64]. PCa was quantitatively detected through overexpressed PCA3 and PSA genes, in urine sediments of men with PCa or BPH, after prostatic massage.…”
Section: Pca3 As a Biomarkermentioning
confidence: 99%
“…In an attempt to improve PCa diagnosis, some studies have demonstrated better results of PCA3 in association with PSA [64, 65], in addition to prostate-specific G-protein coupled receptor (PSGR) [66], a biomarker previously described to be overexpressed in PCa tissue [67]. Other authors found that the combination of PCA3 , PSA, and human kallikrein 2 (hK2) largely improved area under the curve (AUC)-receiver operating characteristic (ROC), especially those patients presenting PSA 4-10 ng/mL [64]. PCa was quantitatively detected through overexpressed PCA3 and PSA genes, in urine sediments of men with PCa or BPH, after prostatic massage.…”
Section: Pca3 As a Biomarkermentioning
confidence: 99%
“…*P < 0.05 produce glucose-6-phosphate [31]. Previous studies have confirmed that the expression of HK2 is significantly upregulated in many cancers and its high expression in cancers is associated with poor prognosis [30,[32][33][34][35]. Administration of HK2 inhibitor, 2-DG, can induce cancer cell death by abrogating intracellular glycolysis.…”
Section: Discussionmentioning
confidence: 97%
“… 95 Zidan et al 96 reported that plasma levels of miRNAs -21, -125b, -126, -141, -143, and -375 were upregulated in patients with prostate cancer compared with individuals without malignancy. Mao et al 97 reported that miRNA-141 in peripheral blood, measured with quantitative real-time PCR, was significantly higher in patients with prostate cancer compared with patients with benign prostatic hypertrophy.…”
Section: Psamentioning
confidence: 99%